Padronização e atividade anti-inflamatória do extrato aquoso de Psittacanthus plagiophyllus Eichl. (Loranthaceae) - BEZERRA, Adrielle Nara Serra (Universidade Federal do Oeste do Pará, 2021)
Abundant in cashew trees of savannah áreas of Alter do Chão disctrict, Santarém, Pará, Brasil, the hemiparasitic species Psittacanthus plagiophyllus Eichl. (Loranthaceae), known as erva-de-passarinho, is popularly used to treat gastritis and various inflammatory conditions. Considering the absence of pharmacological studies with this species in the literature and the importance of research into antiinflammatory drugs of plant origin, the aim of this study was to standardize the extract obtained of P. plagiophyllus leaves and evaluate their antiinflammatory potential in animal model and their in vitro antioxidant capacity. Quality control and standardization of extract and plant drug of P. plagiophyllus were performed in accordance with the criteria of the National Health Surveillance Agency (ANVISA), through the Brazilian Pharmacopoeia 5th edition. To obtaining and standardization of P. plagiophyllus extract, the plant drug was subjected to extraction pilots by different ratios of ethanol and water, followed by determination of total phenols, tannins and flavonoids, in order to select the extractor liquid most suitable to obtain an extract rich in bioactive compounds. After choosing water as extractor liquid and production of aqueous extract of P. plagiophyllus (EAPp) at a temperature of 70 °C, this was lyophilized and subjected to tests of physicochemical characterization recommended by ANVISA and the determination of the chromatographic profile for thin layer chromatography, which indicated the presence of hydrolyzable and condensed tannins, flavonoids and coumarins. The quantification of the phenolic compounds present in the extract showed concentrations of 12,62±0,18% of total phenols, 5,39±0,01% of total tannins, 12,54±0,24% of hydrolysable tannins, 8,37±0,32% of condensed tannins and 1,23±0,02% of total flavonoids. To assess the in vivo antiinflammatory activity of the EAPp, was first employed the model of carrageenan- and dextran-induced paw edema in rats. At doses of 500 and 1000 mg/Kg (p.o), EAPp showed significant (p<0,01) antiedematogenic action in both models, suggesting a possible action on vascular and cellular events of inflammatory response and a suppressive effect on the mediators responsible for the formation of edema. To evaluate the effect of the EAPp on exudation and leukocyte recruitment in response to carrageenan, was used subcutaneous air pouch model. In all doses tested (250, 500 and 1000 mg/kg, p.o), the EAPp inhibited significantly (p<0,01) the total leukocytes and neutrophils migration and reduced exudation in the pouch, at a dose dependent manner. Furthermore, in the in vitro antioxidant activity test by free radical DPPH sequestration method, the EAPp (75 μg/mL) was able to reduce up to 93,13±1,71% the tested radical, which highlights its high antioxidant potential. The observed pharmacological actions may be related to the high content of phenolic compounds in EAPp. These results provide scientific evidence for the popular use of P. plagiophyllus in the treatment of inflammatory disorders.